A comparison of the 10-year properties of converter steel slag activated by high temperature and an alkaline activator. (20th February 2020) - Feng, Jingjing; Sun, Jianwei
Highlights: Hydration products after 10 years are C–A–S–H gel with Q 2 structure and Ca(OH)2 . The activation methods have little influence on the types and morphologies of the products. Adding an activator is better for improving late–stage cementitious properties. Using the two methods simultaneously has a negative influence on the properties. Abstract: This paper aims to study the late–stage cementitious properties of converter steel slag activated under different conditions. Three methods, including an early high–temperature curing, an alkaline activator and application of the two methods simultaneously, were used. Steel slag without an activator at room temperature was selected as the control sample. The long–term (10 years) properties at the same solution–steel slag ratio (0.3), including the characteristics of the hydration products, reaction degree and pore structure, were investigated. The results show that the hydration products consist of a C–A–S–H gel mainly comprising a Q 2 structure and Ca(OH)2 . The different activation methods have little influence on the types and morphologies of the products. Although using an early high–temperature curing or an alkaline activator can reduce the Ca/Si and Al/Si ratios in the gel, using the two activation methods simultaneously can significantly improve the ratios. Adding an alkaline activator is more effective in increasing the amounts of late–stage hydration products, increasing the reaction degree and improving the pore structure than increasing the early curing temperature. Using the two methods simultaneously can reduce the amounts of late–stage hydration products, decrease the reaction degree and deteriorate the pore structure. Therefore, adding an alkaline activator has a more substantial influence on improving the late–stage cementitious properties than increasing the early curing temperature. However, using the two methods simultaneously has a negative influence on the properties.